Farewell : May 14 - June 19 - Bartana, Yael (Cecilia Hillström, 2025)
Solo Exhibition at Cecilia Hillström Gallery We are proud to present 'Farewell', Yael Bartana’s second solo exhibition at the gallery. The show centers around her project for the German Pavilion at the 60th Venice Biennale and expands upon it with new works. ⁠ ⁠ The exhibition opens Wednesday 14 May 17:00–20:00. An artist talk will take place on Saturday 17 May, 15:00, with Nanna Hjortenberg, Director of Gammel Strand.⁠ ⁠ The show takes its title from the video work 'Farewell', which portrays a ceremonial departure for the generation ship 'Light to the Nations', destined for distant galaxies. The ship’s launch marks a radical decision to separate from Earth—a departure from a planet exhausted by human failure – towards an unknown future crucial for humanity’s survival. 'Farewell' is a moment of collective grief and anticipation.⁠
Keywords: Farewell; Venice Biennale; German Pavilion; Generation Ship; Sci-Fi